Language and Nation Crossroads and Connections - Barstad, Guri Ellen; Hjelde, Arnstein; Barstad, Guri Ellen; Hjelde, Arnstein; Kvam, Sigmund; Parianou, Anastasia; Todd, John (2016)
Studies on the relation between language, identity and nation (building) represent a long tradition in linguistic, cultural and political research. In this interdisciplinary anthology, we focus on different aspects of how language is used to shape a nation; by retaining a national identity in the context of emigration, by measures taken to change an existing nation into a new one, by introducing a discourse designed to re-establish a putatively lost nation. Finally, we discuss how nation and identity are shaped in a modern multi-ethnic, multi-lingual and multi-cultural society. The anthology contains articles in English, French and German from political science, history, linguistics, literature and translatology and is written by researchers based in Finland, Greece, Norway and the United Kingdom.